Mechanics of Supplemental Drop Wire and Half‐Pin Fixation Elements in Single Ring Circular External Fixator Constructs. Issue 4 (24th March 2016) - Lewis, Ryan A.; Lewis, Daniel D.; Anderson, Christopher L.; Hudson, Caleb C.; Coggeshall, Jason D.; Iorgulescu, Alex D.; Banks, Scott A.
Abstract : Objective: Evaluate the effects of supplemental fixation elements on the mechanical properties of a single ring circular fixator construct. Study Design: In vitro mechanical testing. Sample population : Five construct configurations (six replicates of each configuration) were used to stabilize a 1.6 cm diameter Delrin rod bone model. Methods: Constructs were assembled using 66 mm complete rings, 1.6 mm olive wires, and 3.2 mm diameter half‐pins. Construct configurations tested were a base single ring construct, constructs with 1 supplemental drop wire or constructs with 1, 2, or 3 supplemental half‐pins. Constructs were loaded in axial compression, caudocranial and mediolateral bending, and torsion. Strain was measured in individual fixation elements during axial loading. Results: A supplemental drop wire or half‐pin significantly increased bending and torsional stiffness. The supplemental half‐pin increased caudocranial stiffness significantly more than placing a drop wire. Placing a 2nd or 3rd pin afforded significantly greater increases in construct stiffness in all modes of loading, with 3 half‐pin constructs having significantly greater axial and caudocranial stiffness than 2 half‐pin constructs. Placing a single supplemental pin induced cantilever bending resulting in angular displacement of the Delrin rod during axial loading and high strain in both the fixation wire secured distal to the ring and the pin. Supplemental half‐pins incrementally reduced strain in all fixation elements and resulted in linear displacement of the Delrin rod during axial loading. Conclusion: If using supplemental half‐pins as fixation elements, insertion of 2 or 3 pins is preferred over a single pin.